Duty on fish: Zooarchaeological evidence from Kastre Castle and customs station site between Russia and Estonia. (19th July 2019) - Lõugas, Lembi; Rannamäe, Eve; Ehrlich, Freydis; Tvauri, Andres
Abstract: The majority of medieval and early modern fish, bird, and mammal remains in Estonia originate from urban contexts, but a promising site for archaeological faunal finds outside the towns appears to be Kastre ( Varbek ) in central‐eastern Estonia. The site was a castle and customs station that belonged to the Tartu ( Dorpat ) bishop and was first founded at the end of the 14th century on the bank of the Emajõgi River, between Lake Peipsi and Tartu town. River traffic was controlled there; inter alia trade between the Hanseatic towns of Novgorod in western Russia and Tartu, historical sources show, "duty on fish" was collected there in the 15th and 16th centuries. Large numbers of fish, mammal, and bird remains were gathered from the castle during archaeological excavations in 2001 and analysed for the current study. Faunal material reflects animal products consumed most probably by the castle staff, whereas the evidence of fish processing in the castle may refer to the value added to fish for resale. Any direct connection to the customs tax by the faunal remains has not been proven but indirectly hypothesized. Thus, a large amount of fish remains including long‐distance imports, together with the evidence of fur processing and presence of farm animals in the castle, may indicate the duty taken on the trade and/or fishing rights on the Emajõgi River.